PENGGUNAAN MEDIA VIDEO DAKWAH UNTUK MENINGKATKAN KESADARAN SISWA PADA KETENTUAN BERBUSANA MUSLIM DAN MUSLIMAH SESUAI SYARI’AT ISLAM - Sumiati Sumiati (Fakultas Ilmu Tarbiyah dan Keguruan Universitas Islam Negeri Raden Fatah Palembang (UIN) Raden Fatah Palembang, 2022)
Islamic education and good manners are the main subjects that are learned at school. Including in class X at the high school level. One of the materials taught is Muslim and Muslimat Dresses are a Reflection of Personality and Self-Beauty. In this material, one aspect that is expected is that students of class X MIPA 2 can increase awareness of Muslim and Muslimat dresses in accordance with Islamic Shari'ah in everyday life. One of the appropriate learning techniques in learning to improve students' understanding is to use Da'wah Video media. Video is an Audio Visual media that displays sound and motion. The messages presented can be factual or fictitious, can be informative, educative, or instructional. In an educational way, videos can convey educational value, educate students and the community to think critically, provide meaningful experiences, and develop and broaden students' thinking horizons. While Da'wah in language means to call, invite, invite, appeal and dish. Da'wah can also be interpreted as a call or invitation. Quoting from Malikah's research in his psychology journal, Soemarno Soedarsono explained that self-awareness is the embodiment of a person's personal identity (attittude) and behavior (behavior) that he has. People with high self-awareness means that they know themselves well. In carrying out this method, children can apply how to dress according to Islamic law not only at school but also at home in everyday life. While the Video method can be used in teaching and learning activities both online and offline. The final result of this research is an increase in student learning outcomes, namely Complete Learning. Therefore, efforts to maximize students' awareness of Muslim and Muslimat Dress is a Reflection of Personality and Self-Beauty with Da'wah Video Media can run smoothly and on target.